Book of Abstracts / International Scientific Conference »Research and Education in Nursing«,June 13th 2019, Maribor, Slovenia (University of Maribor Press, 2019)
Concurrently with the 26th anniversary of the establishment of the Faculty of Health Sciences, we are organizing the scientific conference entitled »Research and Education in Nursing Care«. The conference’s purpose and aim is to present the progress in the field of research for practice and education support, to introduce an interdisciplinary and interprofessional approach in nursing care and health care in Slovenia and abroad and also to show the contribution of core knowledge development. The added value of the conference is the integration of higher education teachers, higher education collaborators and students with the exchange of research findings, models of good practice and innovative ideas. We will present articles from current scientific-research projects, dealing with an effective, safe, humane, patient-friendly and family-orineted nursing.